Meta-Analysis: Effect of Endometriosis and Intrauterine Device Contraceptive on Ectopic Pregnancy - Habibatullah, Afifa Intifadha; Budihastuti, Uki Retno; Widyaningsih, Vitri (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Ectopic pregnancy is an early complication of pregnancy with high morbidity and mortality. Several studies have examined a history of endometriosis and Intrauterine Device Contraceptive (IUD) use as risk factors for ectopic pregnancy, but have shown mixed results. This study aims to analyze the influence of a history of endometriosis and IUD use on the incidence of ectopic pregnancy based on previous primary studies. Subjects and Method: This was a systematic review and meta-analysis conducted with the PRISMA flow diagram guidelines. The article search process was carried out on the PubMed, Google Scholar, Science Direct, SAGE, JSTOR, and Scopus databases, for articles published from 2005 to 2022. The keywords used were: “Endometriosis” AND “Intrauterine Contraceptive Device” OR “Intrauterine Device” OR “IUD” OR “IUCD” AND “Ectopic Pregnancy” OR “Extrauterine Pregnancy” OR “Tubal Pregnancy” OR “Pregnancy Outcomes” OR “Pregnancy Complications” AND “Multivariate” OR “Multivariable” OR “Adjusted Odds Ratio” OR “aOR